Information system design for higher education evaluation based on student's perspective - Tiara Verita Yastica; Muhammad Nashir Ardiansyah; Muhammad Almaududi Pulungan (International Journal of Innovation in Enterprise System, 2023)
The quality of Indonesia's higher education institutions has not excelled compared to Southeast Asiancountries such as Singapore, Malaysia, and Thailand. Based on 2020 data, the percentage of highereducation institutions in Indonesia that have been accredited is 59%. It is crucial to evaluate andimprove the factors that affect the quality of higher education institutions based on the student'sperspective, the primary customer of higher education institutions. This study aims to evaluate thequality of higher education institutions based on students' satisfaction in real-time. Furthermore, thisresearch will propose a design of an information system that can automate the evaluation process. Thefindings of this study can be applied to the existing system, providing information and analysis tosupport the policy-making process.